ANALISIS PENGARUH PERTUMBUHAN PENDUDUK DAN PRODUKTIVITAS LAHAN TERHADAP ALIH FUNGSI LAHAN PERKOTAAN (STUDI KASUS KOTA MARISA) - Irwan Wunarlan; Hasbullah Syaf (Jurnal Perencanaan Wilayah, 2019)
This study aims to show the effect of population growth and land productivity on theconversion of urban land. This study uses data on area size by type of land use per village to measureurban land use. The use of population growth data and land productivity was analyzed using multipleregression and classification typology, the authors found that population growth had a negativeinfluence and land productivity had a positive influence on land conversion. Negative populationgrowth of -3,593 and land productivity of 6,921 will give effect to the conversion of land with an areaof 31,197 Ha. The type of region that experiences land conversion in Marisa City can be classifiedinto three types, namely (1) Areas in the process of land conversion (Marisa Utara) , (2) Areas thatare rapidly shifting land functions (South Marisa, Pohuwato, Teratai, Botubilotahu Indah, Palopo andBulangita), and (3) Areas that have the potential to convert land (Pohuwato Timur). The results of thisstudy indicate that population growth and Land productivity plays an important role in acceleratingthe conversion of urban land in the Marisa City area of Pohuwato Regency.Keywords: population, land productivity, function change, region, city